EMPLOYEE ENGAGEMENT AND EMPLOYEES’ PERFORMANCE IN UNITED NATIONS DEVELOPMENT PROGRAMME, ABUJA, NIGERIA (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2025)
The issue of employees’ engagement has been a serious source of concern in United Nations development programme (UNDP), Abuja, Nigeria. The organization as well as other related institutions is faced with the problems of job engagement, autonomy to work independently, provisions of reward and recognition systems as well as the provision of inclusive work environment opportunities to employees. These conditions gave rise to the emergence of unsuitable employees with lack of the needed requisite skills to pilot the affair of the entity. A condition which has direct bearing in employee performance in the organization. The main objective of the study is to examine the impact of employee engagement on the performance of employees in United Nations Development Programme, Abuja, Nigeria. The survey research design was used in the study and data was collected from primary source with the use of questionnaire. The study population consists of about 251 employees of UNDP, Abuja, which was adopted as the sample size for the study. Both descriptive and inferential statistics was used for data analyses through simple percentage, and mean method. The ordinary Least Square regression method was used to test the formulated hypotheses. The findings show that there is a significance relationship between employees’ engagement and employees’ performance in United Nations Development programme (UNDP), Abuja. The study concluded that autonomy to work independently has a positive significance relationship with employee performance in UNDP, Abuja. It was recommended that the management of United Nations Development Programme (UNDP), Abuja, Nigeria should establish a work inclusive policy which would give guidelines to all stakeholders on how employee engagement will be implemented to foster management commitment toward enhancing employee job satisfaction.